Experience of the joint Master Program with TomskPolytechnic University and Czech Technical University; 11th International Technology, Education and Development Conference (INTED2017), 6-8 March, 2017, Valencia, Spain - Lukutin B. V. Boris Vladimirovich (2017, 2017)
Title screen